Giving voice to the teaching assistant dilemma - Willoughby, Stephen J.; Dunkley, Pamela (Emerald Publishing Limited, 2025)
Whilst teaching Assistants (TAs) are a crucial part of the education workforce, their role and contribution is little understood, even by teachers they work alongside. By giving a voice to TAs, The Teaching Assistant Dilemma helps to tackle this lack of understanding. Highlighting the problems TAs face, not just that their contribution is undervalued, but also that their pay is low and their opportunities for career progression are very limited, the authors suggest changes in both policy and practice to tackle these issues. TAs have a wide history of support for students including specialist roles in special educational needs (SEN), English as an additional language (EAL) or pushing the talented further. They are of vital importance to children but undervalued, financially and professionally, by the institution that employs and deploys them. This text pushes forwards the debate around the effective development of TA professional practice from all sides, including OFSTED, for the benefit of school communities. Willoughby and Dunkley present evidence from TAs in the first instance rather than senior leadership which is a fresh and new perspective. They powerfully argue for TAs to attain a parity of esteem in schools for the significant benefit of all stakeholders, the sector and the country's socio-economic situation overall, providing a clear and honest appraisal of TA policy and suggest possible future developments for advisors and policy makers.